Distribution pattern of different volumes of ropivacaine in ultrasound-guided intertransverse process block: a randomized, blinded, computed tomography imaging study - Chao-wei Wang; Ping Zou; Zu-xiong Zhang; Mao-yan Si; Qin-guo Yi; Li-fang Zhan (BMC Anesthesiology)
Abstract Background Intertransverse process (ITP) blocks showed reliable paravertebral spread in cadaveric studies, but specific distribution patterns, spread pathways, and dose‒effect relationships remain unclear. The aim of this study was to evaluate the distribution patterns of three different volumes of local anesthetic (LA) in ITP block in living humans using computed tomography. Methods Forty-five individuals (18–75 years old) were randomized to receive 0.375% ropivacaine with radiopaque contrast agent at doses of 0.3, 0.4, or 0.5 ml/kg. The primary outcome was the distribution of LA in mediastinal compartments (prevascular, visceral, and paravertebral), retro-superior costotransverse ligament space, erector spinae fascia plane, intercostal space, sympathetic ganglion, costotransverse space, intervertebral foramen, lateral recess, and epidural space. The secondary outcomes included intraoperative and postoperative VAS scores, dermatomal sensory loss, block-related adverse events, and the time required for block administration. Results The spread pattern of local anesthetic after intertransverse process block includes both forward and backward spread. The LA was concentrated in the visceral compartment (77.5%), paravertebral compartment (93.3%), erector spinae fascia plane (97.8%), intercostal space (97.8%), and sympathetic ganglion (88.9%), with occasional spread to other areas. The overall distribution pattern was significantly influenced by patient position (R2 = 0.07, F. Model = 3.43, P = 0.04) rather than anesthetic volume (R2 = 0.03, F. Model = 1.60, P = 0.20) and BMI category (R2 = 0.03, F. Model = 1.36, P = 0.26). The LA was concentrated in the prevascular compartment when the patient position was changed in the prone position (B = 2.45, 95% CI [0.96, 3.95], P = 0.002). There were no differences in secondary outcomes. Conclusions ITP block causes the LA to predominantly spread to the paravertebral compartment, visceral compartment, intercostal space, sympathetic ganglion, and erector spinae fascia plane. Within the range of volumes studied (0.3, 0.4, and 0.5 ml/kg), increasing the LA volume did not result in a wider distribution range; the overall distribution pattern was primarily influenced by patient positioning. Trial registration The trial was registered online on 3 April 2024 in the Chinese Clinical Trial Registry (ChiCTR2400082665).